A descoberta do meio ambiente: Itatiaia e a política brasileira de parques nacionais - Pereira, Márcio Mota (2013)
This study aims to understand how was the creating of national parks in Brazil. For this, we will make a historical and economic retrospective of the activities that culminated in more environmental damage in Brazil as well as a brief survey of established instruments, each in their own time, while responsible for the reduction or even the portrayal of such damages. Among these instruments quoted na tional parks, one of qualities of conservation units established as a methodology for to stop the explorat ion about a specific biome. We will conclude this dissertation with an analysis of the reasons for the inclusion of the first national park in the Brazilian region of the Serra da Man tiqueira. The Itatiaia National Park was established during the first government of President Vargas , strategically located between the major cities of the country showed up at the same time as an area of environmental preservation and enjoyment of vacat ioners, serving to safeguard biota and leisure. He was a model for the other six dozen national parks that are part of our conservation units and continues calling attention by the scenic beauty and environmental diversity that protects.